Redescubrimiento de Pinguicula clivorum Standl. et Steyerm. (Lentibulariaceae), una especie rara de Guatemala y México - Zamudio, Sergio (Instituto de Ecología, A.C., 1997)
The study of type specimens of Pinguicula clivorum Standl. et Steyerm. allowed to prove that this is a valid species and independent from P. lilacina Schltdl. et Cham., with which it has been confused. It is also shown that P. barbata Zamudio et Rzedowski is a synonym of P. clivorum.